Venoarterial Extracorporeal Membrane Oxygenation in Severe Drug Intoxication: A Retrospective Comparison of Survivors and Nonsurvivors. Issue 7 (20th September 2022) - Duburcq, Thibault; Goutay, Julien; Preau, Sebastien; Mugnier, Agnes; Rousse, Natacha; Moussa, Mouhamed D.; Vincentelli, André; Cuny, Jerome; Parmentier-Decrucq, Erika; Poissy, Julien
Abstract : Selecting patients most likely to benefit from venoarterial extracorporeal membrane oxygenation (V-A ECMO) to treat refractory drug-induced cardiovascular shock remains a difficult challenge for physicians. This study reported short-term survival outcomes and factors associated with mortality in V-A ECMO-treated patients for poisoning. Twenty-two patients placed on V-A ECMO after drug intoxication from January 2014 to December 2020 were retrospectively analyzed. The primary endpoint of this study was survival at hospital discharge. Univariate descriptive analysis was performed to compare survivors and nonsurvivors during hospitalization. The overall survival at hospital discharge was 45.4% (n = 10/22). Survival rate tended to be higher in patients treated for refractory shock (n = 7/10) compared with those treated for refractory cardiac arrest (n = 3/12, p = 0.08). Low-flow duration and time from admission to ECMO cannulation were shorter in survivors ( p = 0.02 and p = 0.03, respectively). Baseline characteristics before ECMO, including the class of drugs involved in the poisoning, between survivors and nonsurvivors were not statistically different except pH, bicarbonate, serum lactate, Sequential Organ Failure Assessment, and Survival After Veno-arterial-ECMO (SAVE) score. All patients with SAVE-score risk classes II/III survived whereas 85.7% (n = 12/14) of those with SAVE-score risk classes IV/V died. A lactic acid >9 mmol/L predicts mortality with a sensitivity/specificity ratio of 83.3%/100%. V-A ECMO for severe drug intoxication should be reserved for highly selected poisoned patients who do not respond to conventional therapies. Shortening the timing of V-A ECMO initiation should be a key priority in improving outcomes. Low-flow time >60min, lactic acid >9mmol/L, and SAVE-score may be good indicators of a worse prognosis.